The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1017/s0954579423000135
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the ‘active ingredients’ of socioeconomic disadvantage for youth outcomes in middle childhood

Abstract: Background: Youth experiencing socioeconomic deprivation may be exposed to disadvantage in multiple contexts (e.g., neighborhood, family, and school). To date, however, we know little about the underlying structure of socioeconomic disadvantage, including whether the 'active ingredients' driving its robust effects are specific to one context (e.g., neighborhood) or whether the various contexts increment one another as predictors of youth outcomes. Methods: The present study addressed thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…However, some more contemporary studies suggest people experiencing socioeconomic disadvantage may have equal or greater rates of EDs and disordered eating behaviors than their more advantaged peers (Gard & Freeman, 1996; Mitchison et al, 2014; Reagan & Hersch, 2005). Results in youth have been particularly consistent in showing increased rates of disordered eating among both boys and girls experiencing familial or neighborhood disadvantage in population‐based samples (Carroll et al, 2023; Mikhail et al, 2021, 2023). These findings align with research showing that socioeconomic disadvantage is associated with other negative mental health outcomes closely related to EDs, including anxiety and depression (Mwinyi et al, 2017; Ross, 2000).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…However, some more contemporary studies suggest people experiencing socioeconomic disadvantage may have equal or greater rates of EDs and disordered eating behaviors than their more advantaged peers (Gard & Freeman, 1996; Mitchison et al, 2014; Reagan & Hersch, 2005). Results in youth have been particularly consistent in showing increased rates of disordered eating among both boys and girls experiencing familial or neighborhood disadvantage in population‐based samples (Carroll et al, 2023; Mikhail et al, 2021, 2023). These findings align with research showing that socioeconomic disadvantage is associated with other negative mental health outcomes closely related to EDs, including anxiety and depression (Mwinyi et al, 2017; Ross, 2000).…”
mentioning
confidence: 85%
“…Given limited prior research, our analyses were somewhat exploratory. However, following prior population-based studies in youth (Carroll et al, 2023;Mikhail et al, 2021Mikhail et al, , 2023, we expected to find that lower SES was associated with greater ED symptoms for both women and men during at least some life stages. Based on prior work by Burke et al (2022) in college students, we expected to find similar or stronger associations between lower SES and increased disordered eating in Black participants relative to White participants due to the added psychological burden and enhanced financial stress (e.g., denied employment or housing opportunities) that may result from racial prejudice and discrimination.…”
mentioning
confidence: 91%
“…Multilevel study designs that simultaneously control for family and neighborhood variables also find that externalizing psychopathology such as aggression has small to moderate associations (R 2 range = .08-.18) with variables at the family level and small to moderate associations (R 2 range = .01-.18) with variables at the neighborhood level (Beyers et al, 2003;Romano et al, 2005;Santiago et al, 2011). Other studies have also found significant associations between externalizing psychopathology and sociodemographic characteristics at distinct levels of ecological proximity (Carroll et al, 2023) consistent with Bronfenbrenner's (1988) ecological theory of development. As one example, Romano et al (2005) estimated that 28% of the variance in aggression was collectively explained by individual-, family-, and neighborhood-level variables combined in a multilevel model.…”
mentioning
confidence: 90%